Antagonist coactivation of trunk stabilizer muscles during Pilates exercises - Rossi, Denise Martineli; Morcelli, Mary Hellen; Marques, Nise Ribeiro; Hallal, Camilla Zamfolini; Gonçalves, Mauro; LaRoche, Dain P.; Navega, Marcelo Tavella [UNESP] (Elsevier, 2013)
The purpose of this study was to compare the antagonist coactivation of the local and global trunk muscles during mat-based exercises of Skilled Modern Pilates. Twelve women performed five exercises and concurrently, surface EMG from internal oblique (OI), multifidus (MU), rectus abdominis (RA) and iliocostalis lumborum (IL) muscles was recorded bilaterally. The percentage of antagonist coactivation between local (OI/MU) and global muscles (RA/IL) was calculated. Individuals new to the practice of these exercises showed differences in coactivation of the trunk muscles between the exercises and these results were not similar bilaterally. Thus, in clinical practice, the therapist should be aware of factors such as compensation and undesirable rotation movements of the trunk. Moreover, the coactivation of global muscles was higher bilaterally in all exercises analyzed. This suggests that the exercises of Skilled Modern Pilates only should be performed after appropriate learning and correct execution of all principles, mainly the Centering Principle. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Electromyography; Physiotherapy; Pilates method; Stability